Acute Mastoiditis in Children: Necessity and Timing of Imaging. Issue 1 (January 2016) - Marom, Tal; Roth, Yehudah; Boaz, Mona; Shushan, Sagit; Oron, Yahav; Goldfarb, Abraham; Dalal, Ilan; Ovnat Tamir, Sharon
Abstract : Background: Acute mastoiditis (AM) can be clinically diagnosed, with an option for supplemental imaging: computed tomography (CT) scan and magnetic resonance imaging (MRI). Debate widely exists whether clinical diagnosis alone is sufficient, in view of the risk of missing undetected complications. We sought to study the reasons leading to the performance of an imaging study during AM course. Methods: Medical records of children younger than 8 years who were admitted from 2005 to 2014 with AM were retrospectively reviewed. Data included medical history, signs and symptoms, laboratory results, imaging studies, treatment methods and final outcomes. Results: Eighty-six children were diagnosed with 88 AM episodes. Of the AM episodes, 55 (63%) were in boys and 46 (52%) were in children younger than 2 years. All children were treated with parenteral antibiotics, and 82 (95%) underwent myringotomy on admission. Only 20 (23%) children underwent imaging studies, on the 6th median day. Of those, 20 (100%) children underwent CT scans, and 3 (15%) underwent additional MRI studies. The reasons for imaging studies included suspected subperiosteal abscess (9 of 20, 45%), lack of improvement despite adequate medical therapy (7, 35%) and focal neurological signs (4, 20%). Sixteen (16%) children underwent surgery for these pathologies: subperiosteal abscesses (n = 12, ), jugular vein thrombosis (n = 2), perisinus empyema (n = 2), epidural abscess (n = 2) and Luc abscess (n = 1). Conclusions: Most children presenting with AM can be diagnosed clinically and do well with intravenous antibiotics and myringotomy. CT and MRI imaging should be reserved for children with suspected AM-related intracranial complications. Abstract : Supplemental Digital Content is available in the text.